Characterization of PZT/PVDF Composite Film as Functional Material - De Freitas, Ricardo Luiz Barros; Sakamoto, Walter Katsumi [UNESP]; Freitas, Luciana Paro Scarin; Castro, Fabian [UNESP]; Lima Filho, Antonio P. [UNESP]; Kitano, Claudio [UNESP]; De Carvalho, Aparecido Augusto [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2018)
In this paper, we obtained and characterized a composite film made of lead zirconate titanate (PZT) piezoelectric ceramic and nonpolar polyvinylidene fluoride ( \alpha -PVDF) as a functional material. The scanning electron microscopy results show this composite film to have mixed connectivity due to the agglomeration of some of the PZT particles. The response of the composite to an applied ac voltage at 4110 Hz has a slope of 0.074 nm/V. The measured displacement is in the range of 0-30 nm for electric voltages ranging from 0 to 400 V. The experimental results show the composite performance as an acoustic emission sensor to be in good agreement with the response of a commercial standard microphone in the frequency range of 2-6 kHz. By applying 2 kN of cyclic force at a frequency of 3 Hz, we obtained an 80-V peak signal and calculated a dissipated power equal to 158~\mu \text{W}.
Keywords: Lead zirconate titanate (PZT); non-polar polyvinylidene fluoride (α-PVDF)